2013
DOI: 10.1016/j.str.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Mono-ADP-Ribosylated ARTD10 Substrates by ARTD8 Macrodomains

Abstract: ADP-ribosyltransferases (ARTs) catalyze the transfer of ADP-ribose from NAD(+) onto substrates. Some ARTs generate in an iterative process ADP-ribose polymers that serve as adaptors for distinct protein domains. Other ARTs, exemplified by ARTD10, function as mono-ADP-ribosyltransferases, but it has been unclear whether this modification occurs in cells and how it is read. We observed that ARTD10 colocalized with ARTD8 and defined its macrodomains 2 and 3 as readers of mono-ADP-ribosylation both in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
178
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 52 publications
3
178
0
Order By: Relevance
“…At present there are also no antibodies available to detect mADPr, in contrast to PAR. Recently, we have observed that the macrodomains of ARTD8 are capable to interact with mADPr ARTD10 substrates while PARylated proteins are not recognized 22 . We have now utilized this information and demonstrated that NEMO interacted with ARTD8 macrodomains upon ARTD10-dependent mADPr both in vitro and in cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present there are also no antibodies available to detect mADPr, in contrast to PAR. Recently, we have observed that the macrodomains of ARTD8 are capable to interact with mADPr ARTD10 substrates while PARylated proteins are not recognized 22 . We have now utilized this information and demonstrated that NEMO interacted with ARTD8 macrodomains upon ARTD10-dependent mADPr both in vitro and in cells.…”
Section: Discussionmentioning
confidence: 99%
“…As there are currently no antibodies available currently that allow the detection of mono-ADP-ribosylated substrates, we searched for protein domains capable to bind to this modification. We have identified the macrodomains of ARTD8 as 'reader' modules of mono-ADP-ribosylated ARTD10 substrates 22 . Therefore, we tested whether the macrodomains of ARTD8 interacted with mono-ADP-ribosylated NEMO in vitro.…”
Section: Artd10mentioning
confidence: 99%
“…A protein microarray screen identified over 70 substrates for PARP10-catalyzed MARylation (34), but the extent to which most of these substrates are modified in vivo is unknown. Recently, the macrodomain-containing protein PARP14/ARTD8 was shown to recognize MARylated PARP10 and NEMO, thus acting as a reader for protein MARylation (35,36).…”
mentioning
confidence: 99%
“…This staining with GST-mAf1521 in cells transfected with enzymatically active ARTD10 is in line with ADP-ribosylation events occurring at the level of the ARTD10-containing cell bodies, although it is not possible to discriminate whether the staining is associated with either ARTD10 or GAPDH, or both. Furthermore, the prominent GST-mAf1521-dependent change in the staining of cells seen upon transfection with the active ARTD10 enzyme was completely abolished when the cells were treated with either PJ34 (50 µM; Figure 3, ARTD10 + PJ34), which inhibits ARTD10-dependent ADP-ribosylation of GAPDH (Figure 2C), or with FK866 (10 µM; Figure 3, ARTD10 + FK866), which inhibits Nampt (a key enzyme involved in NAD + biosynthesis) and thus reduces the NAD + levels in cells [45,46]. Thus, these data in addition to confirming that ADP-ribosylation events occur in cell bodies containing the over-expressed ARTD10 [46] also demonstrate that the inhibition of the ART activity of ARTD10 by PJ34 and the decreased levels of NAD + (the cofactor of the ADP-ribosylation reaction) by FK866 resulted in the disappearance of ADP-ribosylated proteins from the cytoplasmic bodies.…”
Section: Maf1521 Allows Visualisation Of the Artd10 Membrane-free Celmentioning
confidence: 99%
“…Furthermore, the prominent GST-mAf1521-dependent change in the staining of cells seen upon transfection with the active ARTD10 enzyme was completely abolished when the cells were treated with either PJ34 (50 µM; Figure 3, ARTD10 + PJ34), which inhibits ARTD10-dependent ADP-ribosylation of GAPDH (Figure 2C), or with FK866 (10 µM; Figure 3, ARTD10 + FK866), which inhibits Nampt (a key enzyme involved in NAD + biosynthesis) and thus reduces the NAD + levels in cells [45,46]. Thus, these data in addition to confirming that ADP-ribosylation events occur in cell bodies containing the over-expressed ARTD10 [46] also demonstrate that the inhibition of the ART activity of ARTD10 by PJ34 and the decreased levels of NAD + (the cofactor of the ADP-ribosylation reaction) by FK866 resulted in the disappearance of ADP-ribosylated proteins from the cytoplasmic bodies. These last results are in line with the concept that the catalytic activity of ARTD10 is not strictly required for the formation of these cell bodies; indeed, other domains of the ARTD10 protein have been demonstrated to be required for formation of cell bodies [46], although ADP-ribosylation/de-ribosylation events can occur within these cell bodies and might have a role in the recruitment of ARTD10 targets.…”
Section: Maf1521 Allows Visualisation Of the Artd10 Membrane-free Celmentioning
confidence: 99%